Trabalho, adoecimento, volta e readaptação dos trabalhadores de enfermagem de um hospital universitário. - Lima, Moara Ludmila Rosa (2018)
The present study aims to understand the process of return to work of the nursing worker after health leave. For this, a bibliographical survey was carried out regarding the rehabilitation process in Brazil, in order to understand how the programs were constructed and applied to the workers. We also applied semistructured questionnaires to 20 nursing workers from the Hospital de Clínicas of the Federal University of Uberlândia, who were separated between the years 2010 and 2015 and who were readapted. We sought to understand the reasons for leaving and to describe the structure of the rehabilitation program present at the Hospital, evaluating the importance and impact of the process on nursing workers, as well as their positive and negative aspects. In the analysis emerged 4 themes: positive aspects of the return, negative aspects of the return, loss of bond and working conditions. Six main sectors were chosen for the application of the questionnaire, due to the progressive number of departures during the period studied. These are: Adult Intensive Care Unit (ICU-Adult); Pediatric Intensive Care Unit (Pediatric ICU); Neonatal Intensive Care Unit (Neonatal ICU); Nursing of Gynecology and Obstetrics; Center for Sterilization Materials (CME) and Emergency Room (PS). The results showed the alarming number of departures from the studied years as well as the fragility of the existing rehabilitation process. We observe a disparity of what is proposed in law of what is actually experienced and executed. The INSS manuals and norms seek the insertion of the readapted worker, but we observed a lack of effective programs of readaptation in the studied places of study. The preparation of managers should be prioritized with the objective of overcoming a perspective of isolation and fragmentation for the construction of a service based on the integration of all stages of the readaptation process. We believe that the return process should involve the worker as an active part of the planning of his return. It is urgent and necessary the development of preventive programs and vigilance in workers' health for the mitigation of risks and sickness of workers.